Audio description of art films: A study on the reception of O grão (The Grain) - Braga, Klístenes Bastos (2018)
This article aims at presenting the results of a research that investigated the reception of a group of people with visual impairment to the audiodescribed version of the film O Grão (The Grain, 2007). The film tells the story of a family in the Brazilian Northeastern sertão, who survives with difficulties. It has looser narrative, with few dialogues, many fixed plans and contemplative takes. Faced with the realization that art film is a challenge even for seeing viewers, we exhibited the audiodescription of The Grain for four participants, two with inborn visual disability and two with low vision. We used as a research instrument a pre-data collection questionnaire, which defined the participants' profile, a free recall protocol, which investigated their understanding of the film, and a guided recall protocol, which dealt with questions focused on the evaluation of the narratological elements of the script. The results pointed to the effectiveness of audio description in promoting the accessibility of visually impaired people to the focused film.